Nonlinear characterization of Mercurochrome dye for potential application in optical limiting - Rathnagiri Krishnamurthy, Rekha; Alkondan, Ramalingam (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
Thermally induced optical nonlinearity of Mercurochrome dye in methanol solution at four different concentrations and as solid films mixed with polymethylmethacrylate (PMMA) has been carried out using a CW Nd-YAG laser at 532 nm as the source of excitation. The optical response was characterized by measuring the intensity dependent refractive index n2 of the medium using the Z-scan technique. The dye exhibited a negative (defocusing) nonlinearity and large nonlinear refractive index of the order of 10–7 cm2/W. The nonlinear refractive index was found to vary with concentration. The third-order nonlinearity of the dye was dominated by nonlinear refraction, which leads to strong optical limiting of laser. Optical limiting characteristics of the dye at various concentrations in solution and film were studied. The result reveals that Mercurochrome dye can be a promising material for optical limiting applications.
Optica Applicata, Vol. 40, 2010, nr 1, s. 187-196
Keywords: optyka; Z-scan; Mercurochrome dye; nonlinear optical (NLO) properties; optical limiting